2019
DOI: 10.4049/jimmunol.1800219
|View full text |Cite
|
Sign up to set email alerts
|

A Prime-Pull-Amplify Vaccination Strategy To Maximize Induction of Circulating and Genital-Resident Intraepithelial CD8+ Memory T Cells

Abstract: Recent insight into the mechanisms of induction of tissue-resident memory (T RM) CD8 + T cells (CD8 + T RM) enables the development of novel vaccine strategies against sexually transmitted infections. To maximize both systemic and genital intraepithelial CD8 + T cells against vaccine Ags, we assessed combinations of i.m. and intravaginal routes in heterologous prime-boost immunization regimens with unrelated viral vectors. Only i.m. prime followed by intravaginal boost induced concomitant strong systemic and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Although we cannot exclude the possibility that the level of circulating antigen-specific T cells contributes to such interval effect, this observation is in agreement with previous finding that the trafficking capacity of activated circulating T cells positively correlates with their freshness, probably due to the transient upregulation of α4β7, the homing receptor for MAdCAM-1 expressed on the endothelial cell surface (32). Interestingly, several most recent studies applying prime-and-pull strategy to induce vaginal TRM used a prime-pull interval up to 3 or 4 weeks (44,46), indicating the generation of TRM from prime-established memory pools. Although newly activated effector T cells have a clear advantage over memory T cells in terms of size of the population, the effect of length of the interval between prime and pull on TRM generation is worth future investigations.…”
Section: Discussionsupporting
confidence: 91%
“…Although we cannot exclude the possibility that the level of circulating antigen-specific T cells contributes to such interval effect, this observation is in agreement with previous finding that the trafficking capacity of activated circulating T cells positively correlates with their freshness, probably due to the transient upregulation of α4β7, the homing receptor for MAdCAM-1 expressed on the endothelial cell surface (32). Interestingly, several most recent studies applying prime-and-pull strategy to induce vaginal TRM used a prime-pull interval up to 3 or 4 weeks (44,46), indicating the generation of TRM from prime-established memory pools. Although newly activated effector T cells have a clear advantage over memory T cells in terms of size of the population, the effect of length of the interval between prime and pull on TRM generation is worth future investigations.…”
Section: Discussionsupporting
confidence: 91%
“…Chen and colleagues have also used YS1646 as a vector to test single- and multi-modality approaches for a bivalent vaccine candidate (Sj23LHD-GST) targeting S. japonicum in a similar murine model [29]. Although some authors have promoted so-called ‘prime-pull’ strategies to optimize mucosal responses (ie: ‘prime’ in the periphery then ‘pull’ to the target mucosa) [50], it is interesting that both the Chen group and our own findings suggest that PO→IM dosing may be the optimal strategy. In the S. japonicum model targeting the long hydrophobic domain of the surface exposed membrane protein Sj23LHD and a host-parasite interface enzyme (glutathione S-transferase or GST), the PO→IM vaccination schedule led to important reductions in both worm numbers (51.4%) and liver egg burden (62.6%) [29].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, follow-up studies to the HPV pseudovirus vaccinations mentioned above, with adenovirus vectors encoding HPV16 E6 and E7, showed that an i.m. prime vaccination with a subsequent vaginal boost was more effective in inducing HPV-specific CD8 + T cells and their trafficking to the cervicovaginal tract than only vaginal vaccination (54,55).…”
Section: Systemic Vaccinationmentioning
confidence: 91%